Role Of Business Players In Moderating Market Orientation And Technology Orientation To Product Innovation In Medan City Culinary SMEs - Yusrita Yusrita; Yusniar Lubis; Efendi Pakpahan; Syaifuddin Syaifuddin (Cita konsultindo, 2023)
The purpose of this study is to determine the direct and indirect effects of Market Orientation and Technology Orientation on Product Innovation through the Competence of Business Actors. This study used a census or simple random sampling, determining the number of samples in this study using the Slovin formula where the population of 21 sub-districts in the city of Medan was 8,104 so the sample using the Slovin formula was 381 if you don't want to use engineerings an mpel acc Idental sampling in a month an n January 2023. The data analysis used is SEM-PLS. The results showed that market orientation and technology orientation had a significant effect on the competence of Culinary Small and Medium Enterprises (SMEs) in Medan City and market orientation, technology orientation, and business competence had a significant effect on Product Innovation in Culinary SMEs in Medan City. Then indirectly the Competence of Business Actors is able to mediate Market Orientation and Technology Orientation towards Product Innovation in Culinary MSMEs in Medan City.